Disaster health literacy for diabetics: A scoping review towards a framework - Somayeh Panahi; Golrokh Atighechian; Maryam Heidarpour; Zahra Heidari; Hasan Ashrafi-rizi (Journal of Education and Health Promotion)
Due to the increasing occurrence of natural disasters, it is essential to prioritize the improvement of health literacy during emergencies, particularly for individuals with chronic illnesses like diabetes who are especially vulnerable in the medical sector. The primary objective of this study was to identify the key themes within an emerging framework for disaster health literacy specifically tailored for diabetics. A scoping review design was selected based on the Arksey and O’Malley framework. The published articles indexed in PubMed, Embase, Scopus, and Web of Science databases were retrieved up to April 2023, applying related keywords. There restrictions were placed in the English language and the study design. Textual analysis method to identify themes in the articles. The research team conducted multiple collaborative sessions to identify the themes related to health literacy during disasters based on a comprehensive review of existing literature. Three challenges were identified during the analysis process. These challenges include the difficulties encountered by diabetic patients in the early stages of disasters, the physical side effects they experience, and the major recommendations for preparedness and initial response. Subsequently, a framework was developed based on the extracted main challenges and the established logical connections between the conceptual codes, achieved through consensus among the research team. The study emphasized the importance of integrating health literacy assessment and training initiatives throughout all stages of the disaster cycle, with a specific emphasis on individuals with diabetes. By implementing such programs, it is anticipated that the overall health literacy of diabetic patients during disasters can be enhanced.